Portfolio - Hogge, Quentin Edward Somerville (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2013)
My initial intention is to try to show how, as a poet in South Africa, I suffer from a creative identity crisis. I am a white English-speaking male. I live surrounded by isiXhosa-speaking people. Is my poetry, or will my poetry be, relevant in the 'New' South Africa? Is English, the language of the colonial oppressors, the appropriate medium in the post-apartheid milieu? Will my subject matter be relevant? These questions and my attempts at answering them, form the basis of the poetry and the portfolio that accompanies the poems. My absorption with finding a creative 'voice', my concerns with the environment and a questioning of what post-apartheid poetry should write about all seem a bit Quixotic, especially to me! But at another level, they are deeply serious. (p. 5.)
Keywords: Poetry; Post-apartheid; Environment; South African poetry (English) -- 21st century; Creative writing (Higher education); English language -- Writing